STRATEGI KEPEMIMPINAN KEPALA SEKOLAH DALAM MENGHADAPI ERA DIGITAL 4.0 - Wening, Muslimah Hikmah; Santosa, Achadi Budi (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2020)
The rapid development of technology needs to be addressed by various schools to focus more on improving human resources. Human resources in Indonesia are very low so it needs to improve the quality of human resources, both in terms of intellectual, spiritual, creativity, morality, and responsibility. All need help from the principal as a leader to realize quality competitiveness. The principal needs his leadership strategy in facing this digital 4.0 era. How the strategy will be used will lead to good change. This study aims to find out how the principal's leadership strategy in dealing with the digital era 4, O. is qualitative research. It can be concluded that the principal's strategy is to improve the quality of human resources in the field of ICT in terms of facilities and infrastructure, openness with developments to deal with things that will happen in the digital 4.0 era, reactions that will be carried out quickly about changes in the 4.0 era, oriented on the process and results, Mastering the 4C formula, namely: critical thinking, creativity, communication, collaboration.